Willingness to pay for hepatitis B vaccination in Selangor, Malaysia: a cross-sectional household survey - Rajamoorthy, Yogambigai; Radam, Alias; Mohd Taib, Niazlin; Ab Rahim, Khalid; Munusamy, Subramaniam; Wagner, Abram L.; Mudatsir, Mudatsir; Bazrbachi, Abdullatif; Harapan, Harapan (Public Library of Science, 2019)
Background: In Malaysia, one million individuals are estimated to be infected with the hepatitis B virus. A vaccine for infants has been compulsory since 1989, whereas those born before 1989 need to spend their own money to be vaccinated in private clinics or hospitals. The aim of this study was to investigate and ascertain the determinants of willingness to pay (WTP) for adult hepatitis B vaccine in Selangor, Malaysia. Methods: In 2016, 728 households were selected through a stratified, two stage cluster sample and interviewed. Willingness to pay for hepatitis B vaccine was estimated using the Contingent Valuation Method, and factors affecting WTP were modelled with logit regression. Results: We found that 273 (37.5%) of the households were willing to pay for hepatitis B vaccination. The mean and median of WTP was estimated at Ringgit Malaysia (RM)303 (approximately US$73) for the three dose series. The estimated WTP was significantly greater in those with higher levels of education, among Malays and Chinese (compared to others, predominantly Indians), and for those with greater perceived susceptibility to hepatitis B virus infection. Other factors-perceived severity, barriers, benefits and cues to action-were not significantly associated with WTP for adult hepatitis B vaccination. Conclusion: Additional resources are needed to cover the households that are not willing to pay for hepatitis B vaccination. More awareness (particularly in regards to hepatitis B virus susceptibility) could change the national perception towards self-paid hepatitis B virus vaccination and increase hepatitis B vaccine coverage.